The plays with the axe in armour of the Anonimo Bolognese (1510-1515) - Daniel Jaquet (Bern Open Publishing, 2021)
This contribution examines an anonymous text (Di Accia armato di tutt'arme ) addressing the handling of the axe for armoured combat, compiled in a two-volume anonymous manuscript collection of the beginning of the 16th c. This collection is of particular interest since it predates the "classical" authors of the Bolognese school of the 16th c. and marks a turning point from an earlier late Medieval tradition. Moreover the inclusion of a text dedicated to armour fighting is equally interesting since this kind of combat tends to fade away from the technical register of the next Bolognese authors. The manuscript is shortly described and the text is presented in a diplomatic edition, with a translation and a reproduction of the manuscript in appendices. The content is described and analysed from a technical and a historical point of view, allowing comparison with other similar treatises, identification of the arms and armour, and discussion of the context of application.